Teaching second grade [a practical resource packed with winning strategies & activities that reach & teach all learners in this very important grade] - SchifferDanoff, Valerie (Scholastic Professional Books, 2000)
"Cross-curricular activities, organizational strategies, management tips, patterns & graphic organizers, literature links, reading & writing mini-lessons, pocket chart ideas."